Integrating depositional facies and sequence stratigraphy in characterizing carbonate reservoirs: Mississippian limestone, western Kansas - Martin, Keithan (Kansas State University, 2015)
The Mississippian-aged St. Louis Limestone of Western Kansas is a carbonate resource play that has been producing oil, gas, and natural gas liquids (NGL) for over 50 years. The Mississippian Limestone is made up of heterogeneous limestones with interbedded layers of porous and non-porous units, abrupt facies changes, and diagenetic alterations. These factors combine to characterize the St. Louis Limestone's internal complexity, which complicates hydrocarbon exploration. This study focuses on improving the understanding of the geometry, distribution, and continuity of depositional facies within Kearny County, Kansas. Petrophysical analysis of a suite of geophysical logs integrated with core provided the basis for establishing facies successions, determining vertical stacking patterns within a sequence stratigraphic framework, and correlating areas of high porosity with a respective facies. The following depositional facies were identified; 1) porous ooid grainstone, 2) highly-cemented ooid grainstone, 3) quartz-carbonate grainstone, 4) peloidal grainstone, 5) micritic mudstone, and the 6) skeletal wackestone/packstone. The porous ooid grainstone is the chief reservoir facies, with log-derived porosity measurements between four and eighteen percent. In areas without available core, depositional facies were predicted and modeled using a neural network analysis tool (Kipling2.xla). Values derived from the evaluated core intervals and their respective geophysical logs served as the framework for the neural network model. This study illustrates the advantages of correlating depositional facies with reservoir quality and correlating those specific facies to geophysical logs, ultimately to create a greater understanding of the reservoir quality and potential within the St. Louis Limestone of western Kansas.
Keywords: Carbonate geology; Petroleum geology; Mississippian limestone; Sedimentary geology; Sequence stratigraphy; Geology; Geology (0372)